Energy efficiency optimization of ore grinding by ball mills in a closed cycle with a single-spiral classifier - Matsui, Anatolii; Kondratets, Vasyl; Abashina, Anastasiia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
Factors are identified whose role in increasing the productivity of ball mills is not fully disclosed. The criterion of optimality in the task of increasing the energy efficiency of ore grinding by ball mills and the influence of these factors on its value. Ways to improve the energy efficiency of ore grinding are proposed.